Engineering the electrochemical temperature coefficient for efficient low-grade heat harvesting - Gao, Caitian (2020)
Low-grade heat to electricity conversion has shown a large potential for sustainable energy supply. Recently, the low-grade heat harvesting in the thermally regenerative electrochemical cycle (TREC) is a promising candidate with high energy conversion efficiency. In this system, the electrochemical temperature coefficient (α) plays a dominant role in efficient heat harvesting. However, the internal factors that affect α are still not clear and significant improvements are needed. Here, α of various Prussian Blue analogues (PBAs) is investigated and their lattice change during cation intercalation is monitored using the ex situ X-ray diffraction (XRD) method. For the first time, it is found that α is highly related to the lattice parameter change. Large lattice shrinkage exhibits a large negative α, while lattice expansion is corresponding to a positive α. These are mainly attributed to the different phonon vibration entropy changes upon cation intercalation in various PBAs. Especially, purple cobalt hexacynoferrate delivers the largest α of −0.89 mV K−1 and enables highly efficient heat conversion efficiency up to 2.65% (21% of relative efficiency). The results of this study provide a fundamental understanding of temperature coefficient in electrochemical reactions and pave the way for designing high-performance material for low-grade heat harvesting.